Daily struggles, shifting moods: The short-term dynamics of income and depression - Nursena Aksünger; Wendy Janssens; Menno Pradhan (Tinbergen Institute, 2025)
A bi-directional relationship between poverty and mental health may create a vicious cycle, wherein economic hardship and psychological distress reinforce each other. We examine the short-term dynamics between income fluctuations and mental well-being using 17 months of weekly financial diaries and monthly depression assessments from 669 adults in rural Kenya. Dynamic GMM estimations show that higher weekly incomes correlate with lower depression scores, particularly by improving cognitionrelated sleep quality and concentration. However, depressive symptoms do not predict subsequent income, challenging the notion of a short-term psychological poverty trap. Additionally, household-level mortality and illness shocks correlate with depression but not income, while job loss predicts immediate income reductions but not depression. COVID-19 containment measures explain both outcomes, slightly weakening the income-depression association. Our findings highlight the potential mental health returns to expanding financial support and safety nets, even if breaking a poverty trap via psychological mechanisms seems unlikely short-term.
Keywords: 330; Armut; Mental Health; Ländlicher Raum; Kenia